(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This study is conducted on patients infected with COVID19 Those who are hospitalized in intensive care units in to AL-Shifa Center at AL-Zahraa Teaching Hospital for the period from December 2021 to March 2021, for age groups (41-80 years) and of both sexes. As 50 swabs samples are collected two swabs for each patient; one for culture and other for PCR after direct extraction for DNA, in order to investigate S. aureus infections associated with the emerging corona virus. During the laboratory diagnosis, in culturing obtained 24 (48%) positive samples for S. aureus. The extent of resistance of some commonly used antibiotics against S. aureus are more resistant to antibiotics and by 100% to isolates a higher sensitivity to 12 antibiotics including rifampicin, vancomycin resist, methicillin and tetracyclin. PCR detection of bacterial pathogens 50 (100%) for 16s RNA, while the mecA genes was 38 (76%). and showed no correlation with ICU admission, mortality, and inflammation markers. Although patients who received antimicrobial treatment were more often admitted to the ICU and had a higher mortality rate, PCR pathogen detection was not significantly related to antimicrobial treatment.